1997
DOI: 10.1002/(sici)1097-0274(199706)31:6<756::aid-ajim13>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

A field investigation of the acute respiratory effects of metal working fluids. I. Effects of aerosol exposures

Abstract: A study of cross‐shift change in pulmonary function was conducted among workers exposed to metal working fluids (MWF) in an automobile parts manufacturing company. Three hundred eighty‐six workers (216 machinists exposed to straight or soluble MWFs, and 170 nonmachinists) were studied for 1 day, performing spirometry at the beginning and end of their shift. Airborne concentrations of inhalable particulate, culturable bacteria, and endotoxin were measured. We observed an approximately threefold increase in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
41
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 11 publications
1
41
0
Order By: Relevance
“…Sprince et al (15) also measured aerosol concentrations using the same type of method in an automobile transmission plant and found the geometric mean of total aerosol to be 0.33 (range 0.04-1.44) mg/m 3 . The mean total aerosol mass quantified with gravimetric analysis was generally <0.5 mg/m 3 in the North American studies (17,31,32). This comparison with recent literature on exposures suggests that the occupational exposures in the Finnish machine shops were compatible with or lower than those in North America.…”
Section: Synthesis With Previous Knowledgesupporting
confidence: 58%
See 3 more Smart Citations
“…Sprince et al (15) also measured aerosol concentrations using the same type of method in an automobile transmission plant and found the geometric mean of total aerosol to be 0.33 (range 0.04-1.44) mg/m 3 . The mean total aerosol mass quantified with gravimetric analysis was generally <0.5 mg/m 3 in the North American studies (17,31,32). This comparison with recent literature on exposures suggests that the occupational exposures in the Finnish machine shops were compatible with or lower than those in North America.…”
Section: Synthesis With Previous Knowledgesupporting
confidence: 58%
“…The same group also found an increased risk of cough, phlegm, and wheeze in relation to current exposure to any metalworking fluid among 1042 machinists and 769 assembly workers from three automobile facilities in the United States (14). Two other cross-sectional studies from the United States (15,17) found increased risks of respiratory symptoms, including throat irritation, cough, phlegm, and chest tightness, among machinists. Thus their results are compatible with those of our study.…”
Section: Synthesis With Previous Knowledgementioning
confidence: 82%
See 2 more Smart Citations
“…Exposure to metal working fluids can cause respiratory illnesses (12,13). Endotoxins and fungi are often present in the air of workplaces using water-based metal working fluids and implicated as causal factors in work-related respiratory illnesses (13,14).…”
Section: Discussionmentioning
confidence: 99%